Vascularized pedicled bone graft from the distal radius supplied by the anterior interosseous artery for treatment of ulnar shaft nonunion: An anatomical study of cadavers and a case report - Hideo Hasegawa (2020)
© 2020 Wiley Periodicals, Inc. Background: A vascularized distal radius graft can be a reliable solution for the treatment of refractory ulnar nonunion. The aim of this study is to establish the anatomical basis of a vascularized bone graft pedicled by the anterior interosseous artery and report its clinical application, using cadaveric studies and a case report. Methods: Fourteen fresh frozen cadaveric upper limbs were used. The branches of the anterior interosseous artery (the 2, 3 intercompartmental supraretinacular artery and the fourth extensor compartment artery) were measured at the bifurcation site. The anatomical relationship between the anterior interosseous artery and motor branches of the posterior interosseous nerve was investigated. An anterior interosseous artery pedicled bone flap was used in a 48-year-old woman with refractory ulnar nonunion. Results: There were two variations depending on whether the 2,3 intercompartmental supraretinacular artery branched off distally or proximally from the terminal motor branch of the posterior interosseous nerve. The proximal border of the graft was located at an average of 10.5 cm (range, 6.5–12.5 cm) from the distal end of the ulnar head in the distal type (57%) and 17.5 cm (range, 9.5–21.5 cm) in the proximal type (43%). In the clinical application, successfully consolidation was achieved 4 months post-surgery. The patient had not developed any postoperative complications until the 2-year postoperative follow-up. Conclusions: The anterior interosseous artery-pedicled, vascularized distal radius bone graft would be a reliable alternative solution for the treatment of an ulnar nonunion located within the distal one-third of the ulna.